Human Capital Dan Kinerja Dwelling Time: Studi Empiris Di Terminal Petikemas Semarang - Widhilestari, Christine; Anggoro, Retno (Politeknik Bumi Akpelni, 2025)
This study aims to analyze the influence of human capital on container dwelling time performance at the Semarang Container Terminal. High dwelling time is an operational issue that can reduce port efficiency and competitiveness, and human resource factors are suspected to play a significant role in influencing this performance. The research method used a qualitative approach with in-depth interviews with five informants, consisting of operational managers, supervisors, and field operators at the TPKS, as well as secondary data analysis in the form of dwelling time reports and human resource profiles. Data analysis used triangulation from observations, interviews, and literature studies to ensure the validity of the findings. The results show that human capital, encompassing four main dimensions experience and technical expertise, coordination and communication, technological adaptability, and problem-solving and decision-making—has a significant influence on dwelling time efficiency. The technological adaptability dimension has the greatest impact, reducing dwelling time by up to 30%, followed by coordination and communication (25%), experience and technical expertise (20%), and problem-solving and decision-making (18%). The study's conclusion confirms that optimizing the four dimensions of human capital can result in a total dwell time reduction of up to 30%, significantly contributing to increasing the competitiveness of Semarang Container Terminal through investment in human resource development.